PENGARUH PEMBERIAN PUDING PISANG MELON DAN AIR KELAPA MUDA TERHADAP PENURUNAN TEKANAN DARAH PENDERITA HIPERTENSI - Eliza, Eliza; Lestari, Ayu; Sumarman, Sumarman; Yunianto, Andi Eka (JURNAL RISET GIZI, 2021)
Background : Hypertension is a condition when systolic blood pressure ≥ 140 mmHg and diastolic blood pressure  ≥ 90 mmHg blood. One of herbal therapies to help lowering blood pressure is by utilizing foods which contain high potassium, such as bananas, melons, and young coconut water.Objective : To analyze the effect of banana melon and young coconut water pudding on lowering blood pressure levels of hypertensive patients at the Palembang Public Health Center.Method : A quasi-experimental study with pre and pos test control group design. The subjects were 60 hypertensive patients at Palembah PHC who were eagerly fulfilled inclusion and exclusion criteria. Data analysis were used t-dependent and t-independent tests to analyze the effect of melon banana pudding and young coconut water with blood pressure.Results : The results showed there was an average decrease in systolic and diastolic blood pressure in the treatment group of 13.07 mmHg (p= 0.000) and 6.93 mmHg (p= 0,000). Consumption of banana melon pudding and young coconut water showed a significant effect on reducing 6.1 mmHg systolic blood pressure (p=0.003) and 4.56 mmHg diastolic blood pressure (p=0,000). T-independent test showed that systolic blood pressure in the treatment and control groups obtained p-0.005 and diastolic blood pressure obtained p-value 0.048.Conclusion : Consumption of banana melon pudding and young coconut water could lower blood pressure levels f hypertensive patients